ANALYSIS OF THE INFLUENCE OF CAPITAL LABOUR INTENSIVE,INVESTMENT, MANAGERIAL OWNERSHIP, OPERATING LEVERAGETHROUGH DIVIDEND AND FINANCIAL LEVERAGE AS INTERVENING VARIABLE ON FIRM VALUE IN INDONESIA NON FINANCIAL SECTOR COMPANIES - Robi Nugraha (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The purpose of this study was to analyze the influence of capital labour intensive, investment, managerial ownership, operating leverage, dividend and financial leverage on the firm value of Indonesia non financial sector companies, the influence of capital labour intensive, investment, managerial ownership, operating leverage variable on dividend and financial leverage of Indonesia non financial sector companies, and the influence of capital labour intensive, investment, managerial ownership, operating leverage variable on the firm value through dividend and financial leverage as intervening variable.The results show that the capital labour intensive, investment, managerial ownership, operating leverage, dividend and financial leverage have significant influences on the firm value of Indonesia non financial sector companies. The capital labour intensive, investment, managerial ownership, operating leverage variable do not have significant influences on dividend. The capital labour intensive, investment, managerial ownership, operating leverage variable have significant influences on financial leverage.With path analysis, the result show the The capital labour intensive, investment, managerial ownership, operating leverage variable do not have significant influence on the firm value of Indonesia non financial sector companies with dividend and financial leverage as intervening variable.Keywords: Capital Labour Intensive, Investment, Managerial Ownership,Operating Leverage, Dividend and Financial Leverage, Firm Value.